Health Security Policies: A Comparative Study Through Constitutional Frameworks and the Insights of Veronica Rodriguez-Blanco - Budiono, Arief; Gulyamov, Said Saidakhrarovich; Nugroho, Heru Santoso Wahito; Al Mamun, Abdullah; Mustaffa, Aminuddin (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
In Indonesia, the 1945 Constitution mandates the establishment of health social security. Similarly, Section 15 of Article II of the Philippines’ 1987 Constitution asserts that the state has a duty to protect and promote the right to health for its citizens. Bangladesh’s Constitution, while not explicit, recognizes healthcare as a fundamental human right under Articles 15 (which addresses the provision of basic necessities) and 18 (which pertains to public health). Through a classic socio-dogmatic research method—a type of normative legal research—this study interprets how these constitutional provisions are implemented in practice. While Indonesia’s constitution clearloy requires the state to ensure health security, the government often falls short, lacking sufficient financial supports. In the Philippines, health security initiatives are gradually expanding but also suffer from inadequate funding. In contrast, Bangladesh has not prioritized health security, focusing instead on food security without emphasizing health as a state responsibility. Applying Rodriguez-Blanco’s theory reveals that Indonesia’s approach to social security leans towards an insurance model due to its reluctance to allocate adequate funds. In the Philippines, there is progress, albeit slow and underfund, while Bangladesh’s lack of health security development stems from its prioritization of basic food needs over health provisions.